Factors associated with body weight status among malay government employees in Penang - Basri, Aina Mardiah (2012)
Steady increase in body weight is becoming a major health problem worldwide. The objective of this cross-sectional study was to determine the factors of body weight status among Malay government employees in Federal Government Building, Penang. The data collection was carried out from May – July 2009. Anthropometric measurements were conducted by measuring body weight, height, waist and hip circumference, fat percentage and blood pressure of the respondents. Body weight and fat percentage was measured by using TANITA Body Composition Analyzer (TBF-306, Japan) while height of the respondents was measured by using SECA Body meter (Vogel & Halke GmbH & Co., Germany). Accelerometer (Suzuken Company Limited, Japan) was used to determine physical activity level (PAL). A set of questionnaire was used to determine socio-demographic information, family medical history, smoking habit, eating behaviors and weight control behaviors 10ml fasting blood had been taken to determine lipid profiles of the respondents. From a total of 233 respondents recruited, 44.6% were male and 55.4% were female. A majority of the respondents (53.2%) were in the range of 18-29 years. More than half of female (72.9%) and male (66.3%) were categorized as obese (body fat percentage was too high). Almost 30% of the respondents were classified as overweight whereas 20.6% of them were classified as obese based on BMI classification. Almost 65% of the respondents categorized as sedentary, followed by active (32.9%) and vigorous (2.4%) according to PAL classification. Compared to other attitudes and strategies in weight control behaviors, outcome expectation for diet and exercise were found to be much prevalent among respondents. More than 70% of the respondents were dissatisfied with current weight and trying to lose weight. Bivariate analysis showed that BMI were associated with age (r=0.340, p=0.000), income (r=0.200, p=0.003), waist circumference (r=0.841, p=0.000), body fat percentage (r=0.665, p=0.000), systolic BP (r=0.268, p=0.000), diastolic BP (r=0.307, p=0.000), triglycerides (r=0.176, p=0.038), high density lipoprotein cholesterol (r=-0.234, p=0.006), PAL (r=-0.353, p=0.000), social support for diet (r=0.229, p=0.000), social support for exercise (r=0.136, p=0.038), social interaction for diet (r=0.141, p=0.031), body weight satisfaction (χ2=22.913, p=0.000) and “attempt to lose weight” (χ2=45.184, p=0.000). Multivariate analysis revealed that PAL was the most robust factor in predicting body weight status of the respondents followed by age and “attempt to lose weight”. Weight management strategies that focus on weight loss maintenance should include physical activity program or nutrition intervention for the obese adults population.